How Animals Communicate - Sebeok, Thomas A.; Sebeok, Thomas A. (Indiana University Press, 1977)
In recent years enormous advances have taken place in the field of animal communication. This two-volume collection of essays by experts of international renown presents the latest developments in three main divisions. The introduction and the first six chapters examine major theoretical issues, including both the phylogeny and the ontogeny of communication, as well as pertinent aspects of language and other forms of human communication. The chief mechanisms of communication are taken up in turn in the next seven chapters. The heart of the book consists of surveys of communicative processes in selected groups of organisms, ranging from octopuses and squids to social insects, birds, dog-like and cat-like animals, whales, and the Great Apes, and a special chapter devoted to man—chimpanzee communication. A taxonomic index of animals is included. Contributors to How Animals Communicate are George W. Barlow, Gordon M. Burg-hardt, René-Guy Busnel, David K. Caldwell, Melba C. Caldwell, James A. Cohen, John F. Eisenberg, Arthur W. Ewing, Michael L. Fine, Roger S. Fouts, Michael W. Fox, A. Gautier, J-P. · Gautier, Frank A.Geldard, Ilan Golani, Donald R. Oriffin, Jack P. Hailman, Bert Hölldobler, Carl D. Hopkins, A. Ross Kiester, Devra G. Kleiman, Hans Klingel, Peter H. Klopfer, Philip Lieberman, James E. Lloyd, Peter Marler, Martin H. Moynihan, Bori L. Olla, John R. Oppenheimer, Daniel Otte, Walter Poduschka, Cheryl H. Pruitt, Randall L. Rigby, Anthony Robertson, Arcadia F. Rodaniche, Jack Schneider, Thomas A Sebeok, Robert E. Silberglied, Kate Scow, Harry H. Shorey, W. John Smith, Richard Tenaza, Fritz R. Walther, Christen Wemmer, Peter Weygoldt, and Howard E. Winn.
Keywords: Zoologie; Kommunikationsforschung; Tiersprache; Aufsatzsammlung; Sprache; Kommunikation; Tiere; Ethologie; Animal communication; Communication animale; Animal Communication; Communication studies